Musical Preferences among Students Aged 9-19: A Study on Musical Genres and Styles - Norbert Szabó; Fanni Földi; Tun Zaw Oo; Gábor Csizmadia; Krisztián Józsa (MDPI AG, 2024)
This study aimed to explore students' musical genre preferences, exploring variations across gender and age groups in Hungary. Additionally, we investigated the relationships among the popularity of musical genres and connections between musical programs and related activities. With the help of stratified sampling, we examined the opinions of students aged 9-19 about each genre (N = 1159) using specific musical examples. In this study, musical genres were classified into four main types based on related music videos, including classical popular music (CPM), rock music (RM), classical art music (CAM), and folk music (FM). Different types of analyses, such as t-tests, one-way and two-way ANOVAs, and correlational analyses such as correlation coefficients (r), chi-square tests, and eta squares, were employed in this study. The results showed that the popularity of the four pieces of music classified as CPM, RM, CAM, and FM had a moderately strong correlation with each other. The correlations between FM, CPM, and RM did not differ from each other, but they showed significantly weaker correlation values than the correlation between FM and CAM. Moreover, significant differences were found in the students' perceptions of the genres based on their gender and age groups. Among the four performances, the girls had a greater preference compared to the boys for each one, except for the folk music piece. The youngest age group (9-12) showed the highest preference for the CPM, although the difference compared to the oldest age group (17-19) was not statistically significant. Therefore, this study is beneficial for music education, focusing on students' genre preferences, including CPM, RM, CAM, and FM.